2012
DOI: 10.1038/aps.2012.87
|View full text |Cite
|
Sign up to set email alerts
|

Emodin, an 11β-hydroxysteroid dehydrogenase type 1 inhibitor, regulates adipocyte function in vitro and exerts anti-diabetic effect in ob/ob mice

Abstract: Aim: Emodin (1,3,8-trihydroxy-6-methylanthraquinone) is a potent and selective inhibitor of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) with the ability to ameliorate metabolic disorders in diet-induced obese mice. In the present study, we investigated the effects of emodin on adipocyte function and the underlying mechanisms in vitro, and its anti-diabetic effects in ob/ob mice. Methods: 3T3-L1 adipocytes were used for in vitro studies. 11β-HSD1A activity was evaluated with a scintillation proximity ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…In addition, it has been reported that adipose ATGL expression and lipolysis are regulated by GC signals (Villena et al, 2004;Berthiaume et al, 2007;Xu et al, 2009;Campbell et al, 2011;Serr et al, 2011;Sano et al, 2012;Wang et al, 2012). As shown in these previous similar studies, we confirmed that cortisone treatment increased the ATGL mRNA level and glycerol release in 3T3-L1 adipocytes (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it has been reported that adipose ATGL expression and lipolysis are regulated by GC signals (Villena et al, 2004;Berthiaume et al, 2007;Xu et al, 2009;Campbell et al, 2011;Serr et al, 2011;Sano et al, 2012;Wang et al, 2012). As shown in these previous similar studies, we confirmed that cortisone treatment increased the ATGL mRNA level and glycerol release in 3T3-L1 adipocytes (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, emodin displayed an inhibitory effect on the high‐level glucose‐induced phosphorylation of ERK 1/2 and p38 MAPK (Gao et al ., 2015). Wang et al demonstrated that long‐term emodin (3 µ m ) administration improved glucose tolerance and ameliorated other metabolic disorders in ob / ob mice by the inhibition of 11β‐HSD1 activity in adipose tissue (Wang et al ., ). Emodin has been reported to exhibit protective effects against diabetic cardiomyopathy by regulating the AKT/GSK‐3β signalling pathway (Wu et al ., ).…”
Section: Pharmacologymentioning
confidence: 97%
“…Preclinical proof of concept for their efficacy in metabolic disease has been obtained in vitro and in vivo. Notably, inhibition of 11βHSD1 in 3T3-L adipocytes inhibits lipolysis and adipogenesis induced by treatment with 11-dehydrocorticosterone (the substrate for 11βHSD1 in rodents, forming active corticosterone), implying that 11βHSD1 inhibition may play an important role in regulating adipose tissue metabolism [80]. In obese, insulin resistant, rodents (e.g.…”
Section: βHsd1 Inhibitorsmentioning
confidence: 99%